Investigating active travel to primary school in Ireland. Issue 6 (30th September 2014) - Daniels, Natasha; Kelly, Colette; Molcho, Michal; Sixsmith, Jane; Byrne, Molly; Nic Gabhainn, Saoirse
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Active travel to school, by walking or cycling, can positively influence children's health and increase physical activity. The purpose of this paper is to investigate the context and promoters and barriers of active travel, and the required actions and actors that need to be involved to address each of these. Design/methodology/approach – Both quantitative and participative research methodologies were employed. The sample consisted of 73 children aged between 11 and 13 years from four primary schools in the West of Ireland. A self-completion questionnaire was followed by a participative protocol conducted with the class groups. Findings – Overall 30.1 per cent of children reported that they actively travelled to school. A greater proportion of children from urban and disadvantaged schools actively travelled. Proximity to the school was the most frequently reported promoter and barrier. The children identified many actors that need to be involved to eliminate the barriers and enact the promoters of active travel to school. They also highlighted the need for a multi-sectorial approach to improve active travel rates in Ireland. Originality/value – This study holds potential value in addressing the continued decline in active travel to school in Ireland as it shares a new perspective on the issue; that of the children. Adopting a participative approach allowed the children to participate in groups and develop the data themselves. The children confirmed that they have a relevant and valuable understanding of the process necessary to address active travel to school as a public health issue in Ireland.